Comparison of free and pedicle conjunctival grafts on the repair of superficial keratectomies. Experimental study with dogs (Canis familiaris - LINNAEUS, 1758) - Morales, Adriana; Laus, José Luiz; Souza, Míriam Siliane Batista de; Santos, Jaime Maia dos; Figueiredo, Florêncio; Valeri, Victorio (Brazilian Journal of Veterinary Research and Animal Science, 1996)
The cornea is exposed to various types of injuries. Because of this, authors have studied different methods for corneal repair. Among these are the free and island conjunctival grafts. In this study, the purpose was to compare these two techniques, with special attention given to surgical procedures and their applicability, effects on corneal healing and post-surgical follow-up. We compared free and island autogenous grafts on superficial experimental keratectomies in 22 dogs. Lamellar, circular lesions were inflicted bilaterally. In one of the eyes a circular free fragment of conjunctiva was applied, and in the other eye, a dissected pedicle of bulbar conjunctiva. The eyes were evaluated clinically by histology and scanning electron microscopy. Results were better for the pedicle grafts, that resulted in lesser degrees of conjunctival reaction and less corneal oedema and neovascularization. This method also showed less cellular infiltration and earlier fibrosis. At scanning electron microscopy, both techniques showed tissue integrity and substitution of the epithelial cells of the graft by corneal epithelial cells, at about the 30th day, though this was more evident in the pediculated one.